ANALYSIS OF THE INDONESIAN HIGH SCHOOL CURRICULUM FOCUSING UPON THE ENGLISH PROGRAM - Arifin Ahka Muhammad (Institut Agama Islam Negeri Palopo, 2017)
The central theme of this paper discusses the current issues in English Language Teaching (ELT) in Indonesian contexts particularly the English curriculum of Indonesian secondary school. It will first explore the historical development of English curriculum in Indonesia including the methods or approaches that have so far been used; this section touches on current directions in Teaching English to Speakers of Other Languages (TESOL) methodology - Task Based Language Teaching (TBLT) - studies that may not be readily adapted by some English teachers in Indonesia. It will then move to the discussion of the goals of Indonesian English curriculum - integrated with Character Education - which could be considered a reflection of needs analysis and its ideologies. Lastly, this paper shows some challenges that could have hindered English language learning and teaching in Indonesia particularly related to the washback of English National Examination held by the Indonesian Government each year at the end of the school term; these challenges may need to be addressed by postgraduate universities that provide a TESOL Master`s programme. It also examines other high-stake assessments that seem to have influenced the directions of the English teaching and learning processes in Indonesian contexts.